1988
DOI: 10.1055/s-0038-1647056
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies Against the Heparin- Dependent Protein C Inhibitor Suitable for Inhibitor Purification and Assay of Inhibitor Complexes

Abstract: summaryTwo different monoclonal antibodies against the heparin- dependent inhibitor of human activated protein C were produced, using cleaved modified inhibitor for immunization and partially purified inhibitor for screening of the hybridomas, One of the antibodies recognized free and complexed forms of the inhibitor in immunoblotting experiments. The other antibody was used to develop an assay for A PC -PCI inhibitor complexes. Using the assay the formation of complexes was studied in plasma, both in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…The monoclonal anti-PCI (M1 1-5) was previously reported to be unsuitable for Western blot analysis (25), and dilutions in buffer of blood and seminal plasma resulted in parallel curves, when assayed with the PCI IRMA. We thus concluded that the IRMA recognized the same antigenic epitope in the two fluids.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The monoclonal anti-PCI (M1 1-5) was previously reported to be unsuitable for Western blot analysis (25), and dilutions in buffer of blood and seminal plasma resulted in parallel curves, when assayed with the PCI IRMA. We thus concluded that the IRMA recognized the same antigenic epitope in the two fluids.…”
Section: Resultsmentioning
confidence: 99%
“…After 60 min, the samples were analyzed simultaneously parathyroid glands, kidney, brain, adrenal gland. A negative for APC-PCI complexes as described (25 shown). This suggests that the PCI-coding transcripts syntheother tissues is shorter than expected from the previously charsized in the male reproductive glands and other tissues may be acterized cDNA from the liver (5) although this transcript identical with the transcript obtained from human liver.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma PCI was first described by Marlar and Griffin as an inhibitor of activated protein C (4) and later purified and characterized by several groups (1,(5)(6)(7). Urinary PCI, purified and characterized by Stump et al, was initially described as a new urokinase (uPA) inhibitor and therefore named plasminogen activator inhibitor-3 (PAI-3) (8).…”
Section: Introductionmentioning
confidence: 99%